Design and Validation of Cognitive Conflict-Deep Learning Based Gamification Teaching Materials Based on Students' Misconception Profiles to Support Conceptual Understanding on Work and Energy - Salsabilla Mulya Putri; Fatni Mufit; Fuja Novitra; Zahra Fathanah (Universitas Syiah Kuala, 2026)
Students' conceptual understanding of work and energy remains low due to the high prevalence of misconceptions, indicating the need for teaching materials that effectively facilitate conceptual reconstruction. Therefore, this study aimed to design and validate cognitive conflict-deep learning-based gamification teaching materials on work and energy. This study employed the educational design research (EDR) approach using the Plomp model, consisting of the preliminary research stage and the development/prototyping stage up to expert review. The research involved 155 twelfth-grade students from two public senior high schools in Padang Pariaman Regency and four physics teachers. Data were collected using a 20-item four-tier multiple choice diagnostic test and teacher interview guidelines. The findings revealed that 80.6% of students experienced misconceptions, 15.3% did not understand the concepts, and only 4.1% demonstrated correct conceptual understanding. The highest misconceptions occurred in kinetic energy, potential energy, the relationship between work and potential energy, and the law of conservation of mechanical energy. Based on these findings, gamification teaching materials integrating the four phases of the cognitive conflict model and the three pillars of deep learning (mindful learning, meaningful learning, and joyful learning) were developed. Validation by three experts using Aiken's V produced an average score of 0.92, indicating that the teaching materials were very valid. Therefore, the developed teaching materials are feasible to proceed to practicality and effectiveness testing to improve students' conceptual understanding of work and energy